2019
DOI: 10.1073/pnas.1906124116
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s disease is a type of amyloidosis featuring accumulation of amyloid fibrils of α-synuclein

Abstract: Many neurodegenerative diseases are characterized by the accumulation of abnormal protein aggregates in the brain. In Parkinson’s disease (PD), α-synuclein (α-syn) forms such aggregates called Lewy bodies (LBs). Recently, it has been reported that aggregates of α-syn with a cross-β structure are capable of propagating within the brain in a prionlike manner. However, the presence of cross-β sheet-rich aggregates in LBs has not been experimentally demonstrated so far. Here, we examined LBs in thin sections of au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 34 publications
8
122
0
Order By: Relevance
“…We have also shown that the droplet state can undergo a maturation process into a gel-like state rich in amyloid structure, which is reminiscent of the pathological state seen in Lewy body pathologies [14,15,60]. This phenomenon is expected on the grounds that the transition from the droplet state to the amyloid state takes place through a maturation process, known as Ostwald ripening [61,62], and it is consistent with the recent report that a-synuclein can form hydrogels [63,64].…”
Section: Discussionsupporting
confidence: 89%
“…We have also shown that the droplet state can undergo a maturation process into a gel-like state rich in amyloid structure, which is reminiscent of the pathological state seen in Lewy body pathologies [14,15,60]. This phenomenon is expected on the grounds that the transition from the droplet state to the amyloid state takes place through a maturation process, known as Ostwald ripening [61,62], and it is consistent with the recent report that a-synuclein can form hydrogels [63,64].…”
Section: Discussionsupporting
confidence: 89%
“…These findings are supported by earlier studies demonstrating the anti-amyloidogenic potential of BME on α-Synuclein [37]. Parkinson's disease is recently being considered as a type of amyloidosis-of which the main neuropathological diagnostic feature is the accumulation of cross-β sheet-rich aggregates of α-Synuclein as Lewy bodies in the brain [38]. The crucial step in the pathogenesis of Parkinson's disease is the aggregation of α-Synuclein [39], which is reportedly attenuated by B. monnieri extract [37].…”
Section: Discussionsupporting
confidence: 82%
“…α-Syn initially localizes to the plasma membrane in yeast, but eventually forms toxic cytoplasmic inclusions that are detergent-insoluble, contain high molecular weight α-syn species, react with the amyloid-diagnostic dye Thioflavin-S, and cluster cytoplasmic vesicles reminiscent of aspects of Lewy pathology in PD (Araki et al, 2019;Gitler et al, 2008;Outeiro and Lindquist, 2003;Shahmoradian et al, 2019;Soper et al, 2008;Tenreiro et al, 2014;Zabrocki et al, 2005). While Hsp104 is unable to antagonize formation of cytoplasmic α-syn foci and return α-syn to the plasma membrane, enhanced variants Hsp104 K358D and Hsp104 K358D:Y257L robustly clear α-syn foci ( Figure 5A, B).…”
Section: α-Syn-specific Hsp104 Variants Differentially Affect Cytoplamentioning
confidence: 99%
“…PD is marked by misfolding of α-synuclein (α-syn), a protein normally found in presynaptic terminals, which may function in synaptic vesicle recycling (Abeliovich and Gitler, 2016;Sun et al, 2019). α-Syn misfolds into toxic oligomers and amyloid fibrils, accumulating in characteristic Lewy bodies in the cytoplasm of dopaminergic neurons that degenerate in PD (Araki et al, 2019;Henderson et al, 2019;Shahmoradian et al, 2019). Indeed, protein misfolding and aggregation unite a spectrum of fatal neurodegenerative diseases (Chuang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%